Pedagogic Strategies and Contents in Medical Writing/Publishing Education: A Comprehensive Systematic Survey - Behrooz Astaneh; Ream Abdullah; Vala Astaneh; Sana Gupta; Romina Brignardello-Petersen; Mitchell A. H. Levine; Gordon Guaytt (MDPI AG, 2024)
Workshops or training sessions on medical writing and publishing exist worldwide. We aimed to evaluate published articles about such workshops and examine both the content and teaching strategies employed. We searched ISI Web of Science, Ovid EMBASE, ERIC, Ovid Medline, and the grey literature. We considered no language, geographical location, or time period limitations. We included randomized controlled trials, before-after studies, surveys, cohort studies, and program evaluation and development studies. We descriptively reported the results. Out of 222 articles that underwent a full-text review, 30 were deemed eligible. The educational sessions were sporadic, with researchers often developing their own content and methods. Fifteen articles reported teaching the standard structure of medical articles, ten articles reported on teaching optimal English language use for writing articles, nine articles discussed publication ethics issues, and three articles discussed publication strategies to enhance the chance of publication. Most reports lacked in-depth descriptions of the content and strategies used, and the approach to those topics was relatively superficial. Existing workshops have covered topics such as the standard structure of articles, publication ethics, techniques for improving publication rates, and how to use the English language. However, many other topics are left uncovered. The reports and practice of academic-teaching courses should be improved.